(untitled) (Journal of Engineering and Health Sciences, 2019)
With the development of mobile computing, the focus of the marketing media has shifted from traditional media to social media. We are no longer solely reliant on the newspapers, radio and television for marketing. In fact, people are inclined to go online on social media every day. One of the popular social media today is WeChat. As a mobile app, WeChat has been widely used for social networking and business purposes. Due to the lack of literature in developing effective strategies in using WeChat in marketing, the present study serves as a groundwork to explore the subject matter in Malaysia. This study investigated the strategies on how to use WeChat as a marketing tool to create awareness of self-branding, which leads to enhanced relationships and increased sales. To conduct this research, qualitative method which involved observations and interviews was used to gather the data. Observations in WeChat groups and WeChat Moments were carried out. Thirty interviews were conducted to elicit the ideas or beliefs from WeChat users who are micro e-marketers. All the data collection was subsequently analysed using content analysis. Results indicated that effective WeChat marketing strategies are composed of four main aspects and they are labelled as WeChat followers strategy, WeChat self-branding strategy, WeChat Moments strategy and WeChat groups marketing strategy. This exploratory study contributes a fundamental knowledge about strategies of using WeChat marketing to address why people buy from you and not others. The research results provided insights into how WeChat can be used as a platform to establish, keep and satisfy the customers; create job opportunities for society and overall, bring welfare to the nation.